2020
DOI: 10.3221/igf-esis.55.11
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study Of Friction Stir Spot Welding (FSSW) For Polymer Materials Case Of High Density Polyethylene Sheets: Experimental And Numerical Study

Abstract: Friction stir spot welding (FSSW) is a very important part of conventional friction stir welding (FSW) which can be a replacement for riveted assemblies and resistance spot welding. This technique provides high quality joints compared to conventional welding processes. Friction stir spot welding (FSSW) is a new technology adopted to join various types of metals such as titanium, aluminum, magnesium. It is also used for welding polymer materials which are difficult to weld by the conventional welding process. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been reported that the rotational speed of the tool along with traverse speed in the second position is the most significant parameter for impact strength [6], elongation percentage [7], and other mechanical properties of the weld [8]. This was positively verified by [9] through experimental and numerical investigation for lap joints of high-density polyethylene (HDPE). Frictional heat decreases with temperature because it depends on the contact pressure between the material and the tool.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, it has been reported that the rotational speed of the tool along with traverse speed in the second position is the most significant parameter for impact strength [6], elongation percentage [7], and other mechanical properties of the weld [8]. This was positively verified by [9] through experimental and numerical investigation for lap joints of high-density polyethylene (HDPE). Frictional heat decreases with temperature because it depends on the contact pressure between the material and the tool.…”
Section: Introductionmentioning
confidence: 83%
“…Among the designed experimental layout for the study 1000 rpm spindle speed resulted in strong weld strength by generating sufficient frictional heat for ABS-ABS weld specimens. Excessive spindle speed leads to overheating of the tool, high heat input, higher inertial forces and grain growth in stir zone, thereby resulting in more welding defects, similar observation by [9][10][11][12]. This condition decreases the weld quality and weld strength.…”
Section: Tensile Testmentioning
confidence: 90%
“…As reported by various researchers, the strength of the FSSW joints is affected by the temperature distribution in the welding region which in turn depends upon three factors: the quality of stirring, the material mixing and the amount of heat developed (Benyerou et al , 2021; Lambiase et al , 2017). The tool geometry affects the stirring, the dwell time and infill percentage affect the material mixing, while the tool rotational speed, plunge depth and material combination would determine the amount of heat developed.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of FSSW of thermoplastics, the process consists of four phases: plunging, stirring, solidifying, and retracting. The friction between the tool and the plates generates the heat required to weld the plates (Benyerou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%